بناء أنموذج قياسي لرصد اثر أزمة الرهن العقاري في عجز الموازنة العامة المصرية (المجلة العراقية للعلوم الاقتصادية, 2018)
The mortgage crisis, which later became the global financial crisis, is hitting all corners of the global economy to include most of the world and different backgrounds and economic persuasions, and, of course with varying degrees. That mortgage crisis and its repercussions made some economists consider it the worst financial crisis since the last century, where this crisis affected all the macroeconomic joints, such as the financial and monetary systems. The payments system, global economic growth rates, the movement of international trade and investment, and the world tourism movement, add to this the impact on the price levels of the main sources of energy.The study focused on the impact of reversals of mortgage crisis on fiscal policy (public budget) in a sample of Arab countries, oil and non-oil, and the focus on this aspect came from the full faith of researcher that the fiscal policy plays a key role in the national economy as a whole, both in terms of its ability to allocate resources among the various economic sectors, or through its influence (direct impact) on the use of the total resources of the national economy, and thus its impact on the levels of aggregate demand, add to this its impact on income policies through what the governments offer of support, grants and social costs which being more frequent during crises. So, based on the above, the public budget, both in the public expenditure and / or general revenues affected by mortgage crisis, and that will be reflected on all economic sectors, so the study will try to construct a econometric model to monitor and measure the impact of those reflections on both sides of the general budget and therefore its impact on the budget deficit. The study divided the sample countries to oil countries and other non-oil to clarify the effect of mortgage crisis re-shocks on the budget deficit in both groups.